Validation of the adjusted global antiphospholipid syndrome score in systemic lupus erythematosus patients in Argentina. (December 2020) - Garcia, Lucila; Velloso, Maria S; Martire, Maria V; Savy, Florencia; Arizpe, Fernando; Garcia, Nadia; Testi, Adriana; Pena, Claudia; Costi, Ana C; Isnardi, Carolina; Capelusnik, Dafne; Mazza, Susana; et al.
Introduction: Assessment of risk both for pregnancy morbidity and thrombosis in the presence of anti-phospholipid antibodies (aPL) is still a challenge in Systemic Lupus Erythematosus (SLE) patients. The Global Antiphospholipid Syndrome Score (GAPSS) takes into account the aPL profile (criteria and non-criteria aPL), the conventional cardiovascular risk factors and the autoimmune antibody profile. An adjusted model of the score (aGAPSS) excluding anti-phosphatidylserine/Prothrombin (aPS/PT), suggests that the score is able to stratify patients for their rate of events making it widely applicable in daily clinical practice. Objective: To validate the aGAPSS in a multicentric cohort of SLE patients in Argentina. Patients and methods: consecutive SLE patients with and with andwithout thrombotic events from seven Rheumatologist centers were included. Traditional cardiovascular risk factors, aPL antibodies and medications received (aspirin, hydroxychloroquine and anticoagulation) were collected. The score aGAPSS was calculated for each patient at the last visit by adding together the points corresponding to the risk factors: 1 for hypertension, 3 for dyslipidemia, 4 for LA and B2GPI (IgM or IgG) antibodies and 5 for aCL (IgM or IgG) antibodies. The discriminative ability of the aGAPSS was calculated by measuring the area under the receiver operating characteristic curve (AUC). Multivariate logistic regression analysis was performed to examine the impact of multiple cardiovascular risk factors and laboratory parameters on the occurrence of thrombosis. Results: Two hundred and ninety-six SLE patients were included. One-hundred and twenty-one patients (40.9%) presented thrombotic and/or pregnancy complications. Median aGAPSS was significantly higher in patients who experienced an event (thrombosis and/or pregnancy morbidity) compared with those without [4 (IQR 1–9) versus 1 (IQR 0–5); p < 0.001]. The best cut off point for the diagnosis of thrombosis and/or pregnancy complications was aGAPSS ≥4. Multivariate logistic regression analysis showed that aCL antibodies [OR 2.1 (95% CI 1.16–3.90); p = 0.015] were an independent risk factors for thrombotic events. Conclusions: This score is a simple tool, easy to apply to SLE patients in daily practice. The use of the aGAPSS could change the non-pharmacologic and pharmacologic treatment in higher risk patients to improve their survival.